Peran Mediasi Kepuasan Kerja Pada Pengaruh Retensi Karyawan Dan Loyalitas Kerja Terhadap Kinerja Karyawan Pada Pt. Cipta Karya Mandiri - Loliyana, Rina; Loliyani, Rini; Isabella, Astrid Aprica (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2024)
The success of a company can be seen from the employee performance in the company. Employee job satisfaction is an indicator of the success or failure of a company. PT.Cipta Karya Mandiri is a company that operates in the financial savings and loans sector. The employee of PT.Cipta Karya Mandiri in 2024 are 94 people. The sample was taken using census techniques as many as 94 people. The analysis techniques used are the classical assumption test, hypothesis test, multiple linear regression test and Moderate Regression Analysis (MRA) test. Based on the results of the analysis, it can be concluded that employee retention has a significant effect on employee performance, and employee loyalty has a significant effect on employee performance partially and employee retention and employee loyalty have a significant effect on employee performance simultaneously. Meanwhile, job satisfaction can mediate employee retention and employee loyalty towards employee performance simultaneously. The better employee retention and employee loyalty, the greater employee commitment and performance. The implications of this research that it is necessary to pay attention to employee retention, work loyalty and employee satisfaction in order to improve employee performance. For further research, it is recommended to add other variables that affect employee performance.